Earth the Motherly Gaia: The Womb and Tomb of All Creatures - Manickam, Thomas (Asian Horizons, 2009)
Order implies relationship. the origin of cosmos from chaos and every formations and transformations thereafter can be summarized into relationship and its breakdown. Whenever and wherever relationship breaks up chaos makes its comeback. Relationship is the foundation of existence, both the visible and the invisible. The environmentalists predict an impending ecological catastrophe on account of various human interventions in the"delicate balancing act of Mother Nature. Prof. Thomas Manickam in this thought provoking article describes ways and means to reestablish the broken relationship between Mother Earth and her Children. Whether to make the womb of our Mother Earth our tomb as well - the choice is ours.